Diuretic Activity of the Aqueous Extract Leaves of Ficus glumosa Del. (Moraceae) in Rats - Fidèle Ntchapda; Djedouboum Abakar; Blaise Kom; Paulin Nana; Christian Bonabe; Maguirgue Kakesse; Emmanuel Talla; Théophile Dimo (The Scientific World Journal)
Experiments were carried out to validate the use of F. glumosa extract as a diuretic in the treatment of hypertension as claimed by traditional healers. The experiments were performed under the same conditions with two synthetic pharmacological diuretics considered as check (Furosemide and Amiloride hydrochlorothiazide). The aqueous extract leaves of F. glumosa accelerated the elimination of overloaded fluid. At the maximum of diuretic response, urinary osmolarity decreased significantly when compared with controls. The single dose treatment of the aqueous extract leaves of F. glumosa has significantly increased urine volume 24 h after administration of the extract. The stability of aldosterone level, the absence of correlation with the plasma levels of sodium, and the increased clearance of free water in the animals receiving the extract show that increased diuresis and natriuresis moderate elevation are tubular in origin. The increase in Na+, K+, and Cl− induced by the extract caused alkalinization of the urine and showed a strong inhibitory effect of carbonic anhydrase and saluretic. These effects were mainly observed at the dose of 375 mg/kg. These observations confirm the traditional use in the treatment of hypertension and support the importance of the conservation of local knowledge as well as the conservation of Cameroonian biodiversity.